Sistem Pengupahan Pada Karyawan dalam Prespektif Islam - marimin, agus; Sumadi, Sumadi; Fitria, Tira Nur (Jurnal Ilmiah Ekonomi Islam, 2024)
This research aims to determine the wage system and the application of the wage system from an Islamic perspective at the manufacturing company PT Anugrah Jaya Utama Karanganyar. This research uses a descriptive method with a qualitative approach. Data collection techniques in this research used literature survey, observation and interview techniques. The result of this research is that the amount of employee salaries is in accordance with work wages, both per day and per month have the same salary. The time for paying salaries is also timely according to Islamic law so that wages are given before the sweat dries. According to the Islamic view, the manufacturing company PT Anugrah Jaya Utama Karanganyar cannot be said to be completely good, because the values in Islam have not been fully fulfilled. Wage determination can be seen from a fair and appropriate perspective when everyone has the same salary and salary can be categorized as a living wage which consists of 3 aspects, namely adequate food, clothing and shelter.